Developing STEAM-Teaching Module in Supporting Students' Literacy Ability in Elementary School - Susanto, Edi; Susanta, Agus; Rusnilawati; Binti Ali, Siti Rahaimah (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Indonesia's efforts to achieve international education standards and address shortcomings in educational attainment are evident in implementing the Merdeka curriculum. However, a major challenge remains limited learning resources that hinder the curriculum's goals. This research addresses this gap by developing a valid, practical, and potentially impactful STEAM (Science, Technology, Engineering, Art, and Math)-based teaching module designed to enhance elementary school students' literacy skills. The research employs a development research methodology with four stages: definition, design, development, and dissemination. The target population consisted of students from state elementary schools in Bengkulu, Indonesia. Data collection utilized a combination of observation, questionnaires, and literacy tests. Qualitative descriptive statistics were employed for data analysis. The findings demonstrate that the developed STEAM module meets the criteria for validity and high practicality. Additionally, the module exhibits the potential for positively impacting students' literacy abilities. The implication of this research is that the STEAM module, through its engaging activities, can increase student motivation in learning, ultimately leading to improved literacy skills.